The Development of Adolescent Academic Self-Efficacy Instruments: Analysis of Rasch Model - Kurniati, Nadiya; Rusmana, Nandang; Suherman, Suherman (Universitas Muhammadiyah Metro, 2023)
Academic self-efficacy is part of social cognitive theory. Academic self-efficacy is an individual's belief in the ability to do a task for achieving optimal goals. The evolution of several developments of self-efficacy instruments found in Indonesia and foreign. But, the limitation of the academic self-efficacy instrument for adolescents encourages the researcher to develop the Adolescents’ Academic Self-efficacy Instrument (AASEI).Therefore, this study aims to develop the Adolescents’ Academic Self-Efficacy Instrument (AASEI) using the RASCH measurement model. The participants in this study were 656 high school seniors aged 15-18 years. The results revealed that the Adolescents’ Academic Self-efficacy Instrument (AASEI) had a good person reliability score (0.86), excellent item reliability (0.99), and a very good Cronbach's Alpha score (0.88). The results of the Rasch analysis revealed that 42 instrument items of Adolescents’Academic Self-Efficacy Instrument fulfill the requirements and can be used to measure adolescent academic self-efficacy in Indonesia.